If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -5) + 8x = 62 + 4x Reorder the terms: 3(-5 + x) + 8x = 62 + 4x (-5 * 3 + x * 3) + 8x = 62 + 4x (-15 + 3x) + 8x = 62 + 4x Combine like terms: 3x + 8x = 11x -15 + 11x = 62 + 4x Solving -15 + 11x = 62 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -15 + 11x + -4x = 62 + 4x + -4x Combine like terms: 11x + -4x = 7x -15 + 7x = 62 + 4x + -4x Combine like terms: 4x + -4x = 0 -15 + 7x = 62 + 0 -15 + 7x = 62 Add '15' to each side of the equation. -15 + 15 + 7x = 62 + 15 Combine like terms: -15 + 15 = 0 0 + 7x = 62 + 15 7x = 62 + 15 Combine like terms: 62 + 15 = 77 7x = 77 Divide each side by '7'. x = 11 Simplifying x = 11
| -3=m/9 | | -c+7=52 | | X+3x-3=-2x+5 | | 3.8x-5.9+7x=7.8x-20.3 | | -3(2a-6)=0 | | x^4+4x^3-12x+15=0 | | 8x+22=152 | | 2x+x+(x-16)=180 | | -2(4y-5)=-14 | | u^2-7u-4=0 | | 2x+6-8x=30-6x | | (-9)*4/3 | | 4(11-2x)=-44 | | F(x)=2xsquared-1 | | 3x+5=2(x-2) | | y+9y=-5 | | 3(6+x)=39 | | 7x+-27=386 | | 1/5(5x-10)=3x-2 | | -18=K-(-1) | | 2x+1=99 | | B=8x^2+20y^3+20xy-6x-7 | | 2(3a-1)=22 | | x^2-60x+30=0 | | 4(5x-3)-5x-1=47 | | -6y+12=13(y+2) | | 6(x+6)-4=6x+2 | | 6x+18=408 | | -163=2x-3(7x+10) | | 3(6+x)=36 | | 8x^2+20y^3+20xy-6x-7= | | 5x-4=4x+11 |